Conductive Hole‐Selective Passivating Contacts for Crystalline Silicon Solar Cells. Issue 16 (21st February 2020) - Wan, Lu; Zhang, Cuili; Ge, Kunpeng; Yang, Xueliang; Li, Feng; Yan, Wensheng; Xu, Zhuo; Yang, Lin; Xu, Ying; Song, Dengyuan; Chen, Jianhui
Abstract: Defect state passivation and conductivity of materials are always in opposition; thus, it is unlikely for one material to possess both excellent carrier transport and defect state passivation simultaneously. As a result, the use of partial passivation and local contact strategies are required for silicon solar cells, which leads to fabrication processes with technical complexities. Thus, one material that possesses both a good passivation and conductivity is highly desirable in silicon photovoltaic (PV) cells. In this work, a passivation‐conductivity phase‐like diagram is presented and a conductive‐passivating‐carrier‐selective contact is achieved using PEDOT:Nafion composite thin films. A power conversion efficiency of 18.8% is reported for an industrial multicrystalline silicon solar cell with a back PEDOT:Nafion contact, demonstrating a solution‐processed organic passivating contact concept. This concept has the potential advantages of omitting the use of conventional dielectric passivation materials deposited by costly high‐vacuum equipment, energy‐intensive high‐temperature processes, and complex laser opening steps. This work also contributes an effective back‐surface field scheme and a new hole‐selective contact for p‐type and n‐type silicon solar cells, respectively, both for research purposes and as a low‐cost surface engineering strategy for future Si‐based PV technologies. Abstract : A passivation‐conductivity phase‐like diagram enables an organic, conductive passivating contact cell concept and dispels the deep‐seated notion that passivation and conductivity are always in opposition and that Si solar cells must use two materials to achieve interface passivation and carrier transport. The device has the advantages of omitting the use of conventional dielectric passivation materials and simplifying the fabrication process.